Al-Jabiri’s Bayani Epistemology As A Basis of Instructional Design Of Arabic Reading Comprehension - Amien, Saiful; Ahmadi, Ahmadi; Riyanto, Ridho (Ijaz Arabi Journal of Arabic Learning, 2023)
The point of this study was to talk about Muhammad Abid al-Jabiri's Bayani approach and how it could be used as an epistemological foundation for designing Arabic instruction, especially in the Arabic reading comprehension course. This research used a type of library research, where the authors collected data from books, journal articles, and other written materials, then coded it and analyzed it through content analysis according to the thematic categories that have been formulated. The findings of this research indicated that Al-Jabiri's Bayani approach, despite all criticism, can be used as an epistemological basis in designing Arabic language instruction, especially in the Reading Comprehension course. Factually, this instructional pattern has become a tradition in traditional pesantrens. However, it can be developed in formal education, including by adopting Reigelut's taxonomy of instruction variables. Namely considering learning condition variables, which included objectives, characteristics of teaching materials, constraints, and learner characteristics. Manipulating instructional method variables, which included three strategies: organizing, delivering, and managing instruction and we are measuring and evaluating instructional outcomes related to effectiveness, efficiency, and attractiveness.